(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The past 17 years is a long enough period to determine whether the elimination of the voivodeships of Koszalin and Słupsk had a positive effect or not on economic and social cohesion of the Middle Pomerania. The main aim of this article is to discuss the Middle Pomerania in terms of historic and present. The following issues were taken into account: transport accessibility, the problem of Middle Pomerania marginalization and its potential socio – economic. The following research method were used: analysis of literature and analysis of data published by Central Statistical Office.